THE CHALLENGES AND PERCEPTIONS OF COMMUNITY CAREGIVERS WITH REGARD TO ANTIRETROVIRAL TREATMENT ADHERENCE OF PATIENTS: A PHENOMENOLOGICAL STUDY - Mokwele, Roslind; Strydom, Herman (Social Work/Maatskaplike Werk, 2017)
Although there is no cure for HIV and AIDS, antiretroviral treatment has transformed this disease into a manageable chronic illness. Relatively little is known about the experiences and psychosocial challenges that community caregivers of HIV and AIDS home community-based care programmes experience in ensuring patent adherence to antiretroviral treatment (ART). This article describes the results of a phenomenological study to explore these perceptions of community caregivers. Focus group discussions were facilitated with community caregivers and they made narrative reflections in journals to gain insight into their everyday world and experiences of dealing with the challenges of patients on antiretroviral treatment, as well as noting their suggestions for interventions to ensure adherence to antiretroviral treatment.